2013
DOI: 10.1371/journal.pone.0073512
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the C-Di-AMP Cyclase dacA Affects Fitness and Resistance of Methicillin Resistant Staphylococcus aureus

Abstract: Faster growing and more virulent strains of methicillin resistant Staphylococcus aureus (MRSA) are increasingly displacing highly resistant MRSA. Elevated fitness in these MRSA is often accompanied by decreased and heterogeneous levels of methicillin resistance; however, the mechanisms for this phenomenon are not yet fully understood. Whole genome sequencing was used to investigate the genetic basis of this apparent correlation, in an isogenic MRSA strain pair that differed in methicillin resistance levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 66 publications
6
93
0
2
Order By: Relevance
“…Besides the declining adenylate energy charge after 20 min of antibiotic treatment (as discussed above), the intracellular c-di-AMP level also significantly decreased. This is reasonable, since this second messenger is thought to be essential for S. aureus (49), and a very low c-di-AMP level is assumed to be involved in a reduced growth rate (50). Interestingly, no significant alteration in the c-di-AMP level was detected under any other antibiotic stress, although this metabolite is assumed to be involved in sensing envelope stress (49).…”
Section: Resultsmentioning
confidence: 88%
“…Besides the declining adenylate energy charge after 20 min of antibiotic treatment (as discussed above), the intracellular c-di-AMP level also significantly decreased. This is reasonable, since this second messenger is thought to be essential for S. aureus (49), and a very low c-di-AMP level is assumed to be involved in a reduced growth rate (50). Interestingly, no significant alteration in the c-di-AMP level was detected under any other antibiotic stress, although this metabolite is assumed to be involved in sensing envelope stress (49).…”
Section: Resultsmentioning
confidence: 88%
“…A single nucleotide polymorphism in the dacA (diadenylate cyclase) gene, which synthesizes the second messenger cyclic di-AMP (c-di-AMP), was detected in the more sensitive cells. Thus, decreasing c-di-AMP levels resulted in reduced autolysis, increased salt tolerance, and reduced basal expression of the cell wall stress stimulon (132). Interestingly, Eagle-type heteroresistance was explained based on reduced repression of mecA transcription and penicillin-binding protein 2= production at a high concentration (128 g/ml) of methicillin, which did not occur at lower concentrations (1 and 8 g/ml).…”
Section: Heteroresistance To ␤-Lactamsmentioning
confidence: 99%
“…Several studies revealed that c-di-AMP is involved in cell wall homeostasis (9,13,30), which may affect the cell shape. Hence, we investigated the morphology of cdaA and cdaR mutant strains by microscopy.…”
Section: Cdar Does Not Affect Synthesis and Membrane Localization Ofmentioning
confidence: 99%
“…Indeed, both depletion and overexpression of cdaA were shown to severely affect the integrity of the cell wall in several Gram-positive bacteria (6,27). Moreover, alterations in the intracellular c-di-AMP pool affect the resistance to cell wall-targeting antibiotics (9,27,28,29,30). The underlying mechanism, explaining how c-di-AMP synthesis is linked to the cell wall integrity, remains to be elucidated.…”
mentioning
confidence: 99%